Animal Models as Tools to Investigate Antidiabetic and Anti-Inflammatory Plants. (4th June 2012) - Eddouks, Mohamed; Chattopadhyay, Debprasad; Zeggwagh, Naoufel Ali
Abstract : Plants have been historically used for diabetes treatment and related anti-inflammatory activity throughout the world; few of them have been validated by scientific criteria. Recently, a large diversity of animal models has been developed for better understanding the pathogenesis of diabetes mellitus and its underlying inflammatory mechanism and new drugs have been introduced in the market to treat this disease. The aim of this work is to review the available animal models of diabetes and anti-inflammatory activity along with some in vitro models which have been used as tools to investigate the mechanism of action of drugs with potential antidiabetic properties and related anti-inflammatory mechanism. At present, the rigorous procedures for evaluation of conventional antidiabetic medicines have rarely been applied to test raw plant materials used as traditional treatments for diabetes; and natural products, mainly derived from plants, have been tested in chemically induced diabetes model. This paper contributes to design new strategies for the development of novel antidiabetic drugs and its related inflammatory activity in order to treat this serious condition which represents a global public health problem.